Design Test Rig for Trailer Connections - A Structured Approach to Developing a Customizable Test Rig for Trailer Connector Verification in Heavy Vehicle Production. - Malmberg, Axel; Gu, Yan (My University, 2025)
Reliable connections between truck and trailer are crucial for maintaining quality and safety standards within truck production. However, the current testing equipment is simplistic and lacks reliability especially when testing nonstandard trucks. This can result in potential production delays and quality issues. This thesis conducted in collaboration with Volvo Trucks, aims to address these issues by developing a specialized, modular test rig specifically for verifying trailer and bodybuilder connectors within Volvo's Customer Adaptations. To identify user needs and market requirements. Stakeholder analyses, structured interviews and observations were performed. The gathered information from these segments formed a basis for requirements and a detailed development phase. Multiple design concepts were evaluated using elimination and Pugh matrices. Finaly resulting in the selection of a modular and flexible solution utilizing Siemens PLC and HMI technology. The developed test rig incorporates robust electrical components and effectively supports all connector types such as VBG, NATO 12-pin, and ISO 12098. The rig also has additional capacity for future integration of pneumatic and hydraulic testing modules. The outcome is a well-documented, scalable concept designed for widespread implementation across Volvo's production facilities, significantly enhancing operational efficiency and overall product quality.
Keywords: Test rig; Trailer connections; PLC; Siemens; HMI; Modular design